Environmental effects on inter-brain coupling: a systematic review - Leahy, Octavia; Kontaris, Emily; Gunasekara, Natalie; Hirsch, Joy; Tachtsidis, Ilias (Frontiers in Human Neuroscience, 2025)
IntroductionEnvironmental factors play a critical role in shaping social interactions, and emerging evidence suggests they may also influence inter-brain coupling (IBC). The main purpose of this paper is to systematically review how environmental variables influence IBC during hyperscanning studies of social interactions. Additionally, this article provides an overview of the experimental protocols employed and identifies both opportunities and challenges within this evolving field.MethodsFollowing PRISMA guidelines, we conducted a systematic literature search in the PubMed and Scopus databases to identify relevant articles. Of the 106 articles initially identified, 7 met the inclusion criteria for this review. The selected articles are original research published up to February 2025, each employing hyperscanning techniques to observe IBC in response to manipulated environmental factors. Articles were excluded based on factors such as the absence of environmental manipulation or not measuring IBC as an outcome.ResultsThe findings reveal that IBC is significantly influenced by environmental factors such as interpersonal distance, background noise, virtual reality, and music. These factors modulate neural synchrony in brain regions critical for social cognition.ConclusionThe limited number of studies in this area reflects both the emerging nature of this research field and the challenges associated with experimental protocols and funding. Despite these limitations, this review underscores the crucial role of environmental factors in shaping IBC during social interactions. This growing field holds great potential for guiding the design of supportive social settings and targeted interventions that promote social cohesion and mental wellbeing.